2019
DOI: 10.2196/11954
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Community Smokers’ Perspectives for Developing a Chat-Based Smoking Cessation Intervention Delivered Through Mobile Instant Messaging: Qualitative Study

Abstract: Background Advances in mobile communication technologies provide a promising avenue for the delivery of tobacco dependence treatment. Although mobile instant messaging (IM) apps (eg, WhatsApp, Facebook messenger, and WeChat) are an inexpensive and widely used communication tool, evidence on its use for promoting health behavior, including smoking cessation, is scarce. Objective This study aims to explore the perception of using mobile IM as a modality to deliver a propo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…The chat-based intervention focused on identifying a value to increase commitment to quit by using ACT, which might be particularly effective in participants who did not have a motivator to quit and not as effective in those who already had a reason to quit. 10 Our results also corroborate previous qualitative findings in the USA that smokers not interested in quitting might be receptive to mHealth support, which was regarded as a novel way to change their smoking behaviour. 32 The mean cost of recruiting a participant and delivering brief advice at baseline was low (US$8•2), suggesting a high scalability of the proactive, lay counsellor-delivered treatment model in places where health-care resources are scarce (eg, in low-income and middle-income countries).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The chat-based intervention focused on identifying a value to increase commitment to quit by using ACT, which might be particularly effective in participants who did not have a motivator to quit and not as effective in those who already had a reason to quit. 10 Our results also corroborate previous qualitative findings in the USA that smokers not interested in quitting might be receptive to mHealth support, which was regarded as a novel way to change their smoking behaviour. 32 The mean cost of recruiting a participant and delivering brief advice at baseline was low (US$8•2), suggesting a high scalability of the proactive, lay counsellor-delivered treatment model in places where health-care resources are scarce (eg, in low-income and middle-income countries).…”
Section: Discussionsupporting
confidence: 90%
“…Details of the design and content of the chat-based intervention have been described elsewhere. 10,21 Briefly, a smoking cessation counsellor interacted with a participant in real time and provided personalised, theory-based cessation support. The acceptance and commitment therapy (ACT) is a counselling model focusing on increasing psychological capacity to accept unpleasant experiences while committing to value-guided behavioural change.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…WhatsApp and WeChat) have become popular because they are cheaper and more attractive than SMS 12 . Our formative qualitative study, which interviewed 21 smokers in 5 focus groups, supports the acceptability and feasibility of mobile instant messaging for chatbased SC support 13 . Our recent randomized controlled trial (RCT) on 1185 community-based smokers has shown that combined 3 months of chat-based support with brief advice intervention (vs brief advice alone) increased validated smoking abstinence (8% vs 5%, p=0.040) and SC service use (17% vs 4%, p<0.001) at 6 months follow-up 14 .…”
Section: Introductionmentioning
confidence: 56%